Historicizing President Épitácio: conceptions of education, society, culture, advances and retrocesses after the construction of the hydroelectric plants - Costa, Michele Cristine da Cruz; Depieri, Eleandro Lopes; Nagay, Lilian Reiko (Revista Hipótese, 2018)
The present experience report was developed from the work accomplished in the discipline History of Education I with the students of the Pedagogy course provided at the IFSP (Federal Institute of Education, Science and Technology of São Paulo) in Presidente Epitácio. The objective was to discuss the historicity concept from the transformations of values, beliefs, educational, cultural and social perspectives that occurred in the city after the construction of the Hydroelectric Power Plant, which began in 1980 and was completed in 2001. The activity was carried out in three procedures: Production of a video which reports people who have experienced the changes that the city has undergone; Compilation of primary sources showing advances and setbacks after the construction of the plant; And “soirées” accompanied by the exhibition of the production. The relevance of the work is justified by demonstrating that historical changes cannot be considered as mere background, but as constitutive of the production of conceptions that helped to understand and modify the present.
Keywords: Historicity; Conceptions of education; Society; culture